Implementación de un fonocardiógrafo digital para el análisis de sonidos cardiacos utilizando la técnica de procesamiento digitales de señales (2022)
A phonocardiography system that allows the acquisition of heart sounds was implemented, where it was developed in a bioinstrument consisting of a hardware part, which consists of parts of a conventional phonendoscope with electronic components, which transmits the signal captured by the computer audio card, which allows analyzing by means of a computational strategy the semi-automatic classification of the normal or pathological signal, debugging noises with the wavelet transform and identifying the high and low frequencies highlighting the frequencies of the R1 and R2 noises, implementing a voice activity detection system (VAD) in order to detect the width of the noises, becoming a support system in the diagnosis with statistical characteristics, shown through an interface made in MATLAB 2022a the diagnosis, with a result of 84% accuracy in the detection of cardiac abnormalities, sensitivity with 82. 3% and 84% specificity, achieving the design of a functional acquisition system with affordable components, with the ability to classify the existence of a cardiac pathology.